PENGUNGKAPAN MODAL INTELEKTUAL DITINJAU DARI KARAKTERISTIK PERUSAHAAN - Muari Sahlan; Ceacilia Srimindarti (SIMAK, 2018)
The purpose of this study is to analyze the effect of firm characteristics on intellectualcapital disclosure. Independent variables in this study were company size,profitability, and leverage. The dependent variable is intellectual capital disclosure.Agency theory is the basic theory used to explain the effect of company size,profitability, and leveragi on intellectual capital disclosure. The population in thisstudy were LQ45 companies that listing in IDX at 2011 - 2012. Sample selectd bypurposed sampling method. The data heve been collected will analyzed usingregression. The result of this study found that company size have a significant effecton intellectual capital disclosure. The profitability and leverage have no effect onintellectual capital disclosure.